How the Jurists Encounter with Man Balagh Traditions and a New Impression of these Traditions - ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã˜ÂªÃ˜Â±Ã›ÂŒ, Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
It is popular among the jurists that by relying on man balagh traditions (whose origin is not clear but acting upon them is rewarding), one can make judgments on matters that some invalid ordinances and traditions denote the desirability of acting upon them. Employing these traditions with a legal and uá¹£Å«lÄ« approach, they concluded that whatever is precondition in traditions denoting the obligatory ordinances are not precondition in traditions denoting the non-obligatory ordinances. In the meantime, by deliberating on the details and content of these traditions and studying other evidences, it becomes clear that their contexts are related to the Divine reward and punishment and are more of theological and ideological tone and cannot be proofs for cancellation of the preconditions for the authority of traditions denoting preferable religious acts and virtues; and thus, giving fatwa for desirability (or aversion), like giving fatwa for obligation or unlawfulness, requires valid proof.